2003
DOI: 10.1590/s1519-69842003000200020
|View full text |Cite
|
Sign up to set email alerts
|

Cladocera fauna composition in a river-lagoon system of the upper Paraná River floodplain, with a new record for Brazil

Abstract: Cladocera communities were studied in lotic and lentic environments of the Upper Paraná River floodplain, State of Mato Grosso do Sul, Brazil. A total of 63 species of Cladocera were identified in 108 samples. Of these, 24 species are considered new records for that floodplain, and one is a new record for Brazil. Chydoridae was the most representative family with 19 genera and 39 species.Key words: Cladocera, species richness, floodplain, Upper Paraná River. RESUMO Composição de cladóceros em um sistema rio-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 10 publications
2
32
0
4
Order By: Relevance
“…In freshwater, the species number is greater, since 26 species were found in lakes of reservoirs by Sampaio et al (2002); in rivers, 30 species were found by Neves et al (2003) and 63 species by Serafim Jr. et al (2003). The results of the present study are expected since this is a transitional environment.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…In freshwater, the species number is greater, since 26 species were found in lakes of reservoirs by Sampaio et al (2002); in rivers, 30 species were found by Neves et al (2003) and 63 species by Serafim Jr. et al (2003). The results of the present study are expected since this is a transitional environment.…”
Section: Discussionsupporting
confidence: 47%
“…The species of cladocerans (Table 1) found in the study area are typical of marine and estuarine environments (Coelho-Botelho et al, 1999;Lopes, 1996;Montú, 1980;Nogueira et al, 1999;Valentin & Marazzo, 2003;Marazzo & Valentin 2004), but most are from freshwater environments (Elmoor-Loureiro, 1997;Elmoor-Loureiro et al, 2004;Hann & Zrum, 1997;Montú, 1980;Neves et al, 2003;SantosWisniewski et al, 2002;Sampaio et al, 2002;Serafim Jr. et al, 2003).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Species invasions represent one of the most urgent threats to the integrity of freshwater ecosystems (Havel et al, 2005a) since invaders may cause the extinction of vulnerable native species through predation, grazing, since the 1980s (Lansac-Tôha et al, 1992;1993;1997;2004;Sendacz, 1997;Serafim Jr. et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Constancy index (S).The presences and replication of all individuals were calculated according to [11]. The species richness index (D*) was collocated monthly according to [12].…”
Section: Ecological Indicesmentioning
confidence: 99%